Multiple Ehrlichia chaffeensis genes critical for persistent infection in a vertebrate host are identified as nonessential for its growth in the tick vector; Amblyomma americanum - Jaworski, Deborah C.; Wang, Ying; Nair, Arathy; Liu, Huitao; Ganta, Roman R. (Frontiers in Cellular and Infection Microbiology, 2023)
Ehrlichia chaffeensis is a tick-transmitted monocytic ehrlichiosis agent primarily causing the disease in people and dogs. We recently described the development and characterization of 55 random mutations in E. chaffeensis, which aided in defining the critical nature of many bacterial genes for its growth in a physiologically relevant canine infection model. In the current study, we tested 45 of the mutants for their infectivity ability to the pathogen’s tick vector; Amblyomma americanum. Four mutations resulted in the pathogen’s replication deficiency in the tick, similar to the vertebrate host. Mutations causing growth defects in both vertebrate and tick hosts included in genes coding for a predicted alpha/beta hydrolase, a putative dicarboxylate amino acid:cation symporter, a T4SS protein, and predicted membrane-bound proteins. Three mutations caused the bacterial defective growth only in the tick vector, which represented putative membrane proteins. Ten mutations causing no growth defect in the canine host similarly grew well in the tick vector. Mutations in 28 genes/genomic locations causing E. chaffeensis growth attenuation in the canine host were recognized as non-essential for its growth in the tick vector. The tick non-essential genes included genes coding for many metabolic pathway- and outer membrane-associated proteins. This study documents novel vector- and host-specific differences in E. chaffeensis for its functional gene requirements.